2020
DOI: 10.26633/rpsp.2020.166
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity patterns among COVID-19 deaths: proposal for the construction of etiological models

Abstract: Objectives. To describe patterns of multimorbidity among fatal cases of COVID-19, and to propose a classification of patients based on age and multimorbidity patterns to begin the construction of etiological models. Methods. Data of Colombian confirmed deaths of COVID-19 until June 11, 2020, were included in this analysis (n=1488 deaths). Relationships between COVID-19, combinations of health conditions and age were explored using locally weighted polynomial regressions. Results. The most frequent health condi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 35 publications
4
21
1
3
Order By: Relevance
“…Few studies to date have explored the combined and additional effect of obesity on COVID-19 severity. 13 31 A study investigated the patterns of multimorbidity among fatal cases of COVID-19 in Colombia. 31 Similar to our study, the authors found that obesity alone or with other diseases was associated with a higher risk of COVID-19 fatality among young people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies to date have explored the combined and additional effect of obesity on COVID-19 severity. 13 31 A study investigated the patterns of multimorbidity among fatal cases of COVID-19 in Colombia. 31 Similar to our study, the authors found that obesity alone or with other diseases was associated with a higher risk of COVID-19 fatality among young people.…”
Section: Discussionmentioning
confidence: 99%
“…13 31 A study investigated the patterns of multimorbidity among fatal cases of COVID-19 in Colombia. 31 Similar to our study, the authors found that obesity alone or with other diseases was associated with a higher risk of COVID-19 fatality among young people. Furthermore, a populationbased study in Mexico observed that the addition of obesity to any number of comorbidities significantly Open access increased the risk of COVID-19 lethality.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty has been linked to infection, 16 severity, 16 17 geographic differences in severity and mortality by MM, 18 prompting a renewed focus on improving global health and access to care, probabilistic modelling, 19 the triage of care and shielding of the most vulnerable. 20 This study presents an important contribution to this developing literature with a comprehensive set of prevalence estimates for MM in eastern Europe. MM is a growing global health problem affecting all nations regardless of wealth.…”
Section: Open Accessmentioning
confidence: 99%
“…Few studies to-date have explored the combined and additional effect of obesity on COVID-19 severity. 13,28 A study investigated the patterns of multimorbidity among fatal cases of COVID-19 in Colombia. 28 Similar to our study, the authors found that obesity alone or with other diseases was associated with a higher risk of COVID-19 fatality among young people.…”
Section: Discussionmentioning
confidence: 99%
“…13,28 A study investigated the patterns of multimorbidity among fatal cases of COVID-19 in Colombia. 28 Similar to our study, the authors found that obesity alone or with other diseases was associated with a higher risk of COVID-19 fatality among young people. Furthermore, a population-based study in Mexico observed that the addition of obesity to any number of comorbidities significantly increased the risk of COVID-19 lethality.…”
Section: Discussionmentioning
confidence: 99%